Comparative Analysis on the Performance of a PDMS-Based Electromagnetic Vibrational Energy Harvester (EM-VEH): Functionality Test on Rotating Machinery - Nur Indah; Jumril Yunas; Azrul Azlan Hamzah; Rhonira Latif; Nanang Sudrajat; Subekti (International Journal of Nanoelectronics and Materials (IJNeaM), 2026)
This study aims to analyze the performance of an energy harvester prototype consisting of a Polydimethylsiloxane (PDMS) membrane and electromagnetic components. The working principle of the energy harvester is to convert vibration energy into low-power electricity. The prototype was tested under various conditions, including a dynamic rotor engine, a motorcycle engine, and a Boeing 737-600 aircraft turbine. Vibration measurements under different conditions were obtained using a CF360A FFT analyzer as the excitation source on the energy harvester prototype. At the same time, the output voltage was recorded with a Hantek 20 MHz 2-channel digital oscilloscope connected to a PC. The results showed that with a dynamic rotor engine, the energy harvester prototype produced the highest output voltage of 0.989 Volts at 40 Hz (14,800 RPM). While with an excitation frequency of 200 Hz, it produced a much lower voltage (0.25 V) on the Boeing 737-600 aircraft turbine. This shows that the prototype is effective at low excitation frequencies for rotating machines.